Occupational handling of nickel nanoparticles: A case report. Issue 9 (8th May 2014) - Journeay, W. Shane; Goldman, Rose H.
<x xml:space="preserve">Abstract</x> A 26‐year‐old female chemist formulated polymers and coatings usually using silver ink particles. When she later began working with nickel nanoparticle powder weighed out and handled on a lab bench with no protective measures, she developed throat irritation, nasal congestion, "post nasal drip, " facial flushing, and new skin reactions to her earrings and belt buckle which were temporally related to working with the nanoparticles. Subsequently she was found to have a positive reaction to nickel on the T.R.U.E. patch test, and a normal range FEV1 that increased by 16% post bronchodilator. It was difficult returning her to work even in other parts of the building due to recurrence of symptoms. This incident triggered the company to make plans for better control measures for working with nickel nanoparticles. In conclusion, a worker developed nickel sensitization when working with nanoparticle nickel powder in a setting without any special respiratory protection or control measures. Am. J. Ind. Med. 57:1073–1076, 2014. © 2014 Wiley Periodicals, Inc.